The World Bank in Nepal, 2003-2008 : Country Program Evaluation - Independent Evaluation Group (Washington, DC: World Bank, 2015)
This report evaluates International Development Association (IDA) support to Nepal during 2003-2008. IDA’s overarching goal during this period was to support the Government’s efforts to reduce poverty and improve human well-being. IDA focused on helping to foster broad-based growth, social development, social inclusion, and good governance. The evaluation highlights the need to introduce greater realism into the country assistance strategy, and to retain flexibility to adjust to changing circumstances. It also stresses the need to consult widely and continually with national stakeholders and development partners. In addition, it points to the importance of making agriculture and rural development central to the program. The evaluation also focuses on the significance of designing and implementing a mechanism to systematically track the impact of the Poverty Alleviation Fund and adjust its design to enhance benefits to the poor. Finally, supporting reforms in public finance management through policy based lending or (if the prerequisites for budget support cannot be met) a sector-wide approach is also a key.